Fairness, Price Stickiness, and History Dependence in Decentralized Trade - Christian Korth; Stefan Napel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
The paper investigates price formation in a decentralized market with random matching. Agents are assumed to have subdued social preferences: buyers, for example, prefer a lower price to a higher one but experience reduced utility increases below a reference price which serves as a common fairness benchmark. The strategic equilibrium reflects market fundamentals, but it is markedly less sensitive to the buyer-seller ratio near the fair price benchmark. Prices may be sticky around very different reference levels in markets with otherwise identical fundamentals. The implied history dependence turns out to be mitigated rather than exacerbated by friction.
Keywords: C78; D49; D63; C91; 330; random matching; price stickiness; social preferences; history dependence; reference dependence; Preisrigidität; Marktmechanismus; Matching; Theorie